2012
DOI: 10.1007/s00216-012-6049-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of egg-based model wall paintings by use of an innovative combined dot-ELISA and UPLC-based approach

Abstract: The chemical analysis of egg-based wall paintings-the mezzo fresco technique-is an interesting topic in the characterisation of organic binders. A revised procedure for a dot-enzyme-linked immunosorbent assay (dot-ELISA) able to detect protein components of egg-based wall paintings is reported. In the new dot-ELISA procedure we succeeded in maximizing the staining colour by adjusting the temperature during the staining reaction. Quantification of the colour intensity by visible reflectance spectroscopy resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…(Florence, Italy), through the AccQ•Tag Ultra Performance Liquid Chromatography, according to Potenza et al . ().…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…(Florence, Italy), through the AccQ•Tag Ultra Performance Liquid Chromatography, according to Potenza et al . ().…”
Section: Methodsmentioning
confidence: 97%
“…The concentrations of amino acids in the supernatants were measured by Espikem S.r.l. (Florence, Italy), through the AccQ•Tag Ultra Performance Liquid Chromatography, according to Potenza et al (2013).…”
Section: Analysis Of Amino Acidsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] In recent years, immunological techniques have attracted increasing attention by those working in cultural heritage. For example, milk residues, 18,19 protein-bound materials and organic bones have been detected, [20][21][22][23][24][25] and all of these studies have demonstrated that immunoassays have the potential to identify and localize the proteins in archaeological materials both rapidly and effectively. However, most of the antibodies used in these immunoassays are readily commercially available "off-theshelf", and the need for tailored antibodies for targeted cultural heritages with high sensitivity and specificity is increasingly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Different analytical methods have been proposed to identify and quantify IgY from egg yolk: ELISA; HPLC [6][7][8]; a biosensor based on surface plasmon resonance [9]; a nanostructured sensor based on electrochemical detection [10]; an electrochemical immunoassay based on electrodes arrays [11]; fluorescence switch assay [12]; or resonance light scattering [13].…”
Section: Introductionmentioning
confidence: 99%